Enhanced Microwave Absorption of Quartic Layered Epoxy-Mwcnt Composite for Radar Applications. Issue 4 (July 2017) - Naidu, M. K.; Ramji, K.; Santhosi, B. V. S. R. N.; Shami, TC; Baskey, Himangshu B; Satyanarayana, B.
In this paper we presented the electromagnetic analysis of multilayered Radar Absorbing Structure (RAS) composed of Multi-Wall Carbon Nano Tubes (MWCNTs) with different weight percentages. The complex permittivity and permeability of MWCNT/epoxy composites with different wt% are analysed and the microwave absorbing characteristics are evaluated. The permittivity and permeability of MWCNT composites increased with increase in MWCNT concentration. Absorption properties like reflection loss of multilayered RAS are estimated analytically using electromagnetic wave theory for different layers and with different layer order based on impedance matching condition. The quartic layer MWCNT/epoxy composite achieves a better microwave absorption when compared to other multilayer RAS. The microwave absorption was attributed to dielectric loss of the material. The simulated quartic layer RAS is fabricated and validation of reflection loss is done experimentally using free space measurement technique. From free space measurement the minimum reflection loss in entire X-band is observed to be approximately −12 dB (95% of absorption), −15 dB (97% of absorption), with 3 GHz band width, −20 dB (99% of absorption) with 2 GHz bandwidth and maximum peak of - 44 dB at 11.5 GHz. Hence the composite material has great potential of application as highly efficient microwave absorber.